Consumer Protection in Acupuncture Practice at L Beauty & Health Clinic Jakarta - Prayuti, Yuyut; Lesmana, Lilis Christine; Dwinijanti, Lenny (Journal of Law, Politic and Humanities, 2025)
Acupuncture practice is a top choice for many consumers at Klinik L BEAUTY & HEALTH JAKARTA, especially Therapist Amelia Kurniasari, S.Tr.Akup. However, concerns about consumer protection in this sector are still relevant. This study aims to explore aspects of consumer protection in acupuncture practice at this clinic. Using a qualitative approach, we interviewed consumers and analyzed online comments, and conducted an audit of the clinic's compliance with applicable regulations. The results revealed positive consumer perceptions of acupuncture services, but also a need for increased transparency, information and legal protection. The importance of ethical standards and regulatory compliance played a major role. This study provides insights for health practitioners and law enforcement to improve consumer safety and protection in acupuncture practice.